Posttranslational modification of Elongation Factor P from Staphylococcus aureus. Issue 7 (16th June 2020) - Golubev, Alexander; Negroni, Luc; Krasnovid, Filipp; Validov, Shamil; Yusupova, Gulnara; Yusupov, Marat; Usachev, Konstantin
Abstract : Antibiotic‐resistant Staphylococcus aureus is becoming a major burden on health care systems in many countries, necessitating the identification of new targets for antibiotic development. Elongation Factor P (EF‐P) is a highly conserved elongation protein factor that plays an important role in protein synthesis and bacteria virulence. EF‐P undergoes unique posttranslational modifications in a stepwise manner to function correctly, but experimental information on EF‐P posttranslational modifications is currently lacking for S . aureus . Here, we expressed EF‐P in S . aureus to analyze its posttranslational modifications by mass spectrometry and report experimental proof of 5‐aminopentanol modification of S . aureus EF‐P. Abstract : Elongation Factor P (EF‐P) is a conserved protein involved in balance regulation, polyproline motif‐containing proteins, stress resistance and virulence. The interaction between the EF‐P posttranslational modification and the CCA end of the acceptor stem of the initiator tRNA growing peptide allows it to be properly evacuated from the ribosome. We performed mass spectrometry analysis of EF‐P from S . aureus and identified the presence of 5‐aminopentanolation.